2009
DOI: 10.2967/jnumed.109.064360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cerebrospinal Fluid Markers to11C-PiB and18F-FDDNP Binding

Abstract: The purpose of this study was to investigate the potential relationships between cerebrospinal fluid (CSF) measurements of b-amyloid-1-42 (Ab ) and total tau to 11 C-Pittsburgh compound B ( 11 C-PiB) and 2-(1-f6-[(2-18 F-fluoroethyl)(methyl)amino]-2-naphthylgethylidene) malononitrile ( 18 F-FDDNP) binding as measured using PET. Methods: A total of 37 subjects were included, consisting of 15 patients with Alzheimer disease (AD), 12 patients with mild cognitive impairment, and 10 healthy controls. All subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
97
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 32 publications
17
97
3
Order By: Relevance
“…However, one study found that CSF Ttau correlates with postmortem tangle load (Tapiola et al 2009), suggesting that the release of tau specifically from degenerating tanglebearing neurons may contribute to the CSF level of T-tau. Consistent with this idea, binding of 18F FDDNP, an agent that is reported to label both plaques and tangles, positively correlates with CSF T-tau levels (Tolboom et al 2009).…”
Section: Fluid Biomarkers and The Brainmentioning
confidence: 79%
See 1 more Smart Citation
“…However, one study found that CSF Ttau correlates with postmortem tangle load (Tapiola et al 2009), suggesting that the release of tau specifically from degenerating tanglebearing neurons may contribute to the CSF level of T-tau. Consistent with this idea, binding of 18F FDDNP, an agent that is reported to label both plaques and tangles, positively correlates with CSF T-tau levels (Tolboom et al 2009).…”
Section: Fluid Biomarkers and The Brainmentioning
confidence: 79%
“…The development of Ab ligands suitable for positron emission tomography (PET) has enabled direct visualization of fibrillar Ab load in the brain in living individuals. Studies have consistently found a relationship between in vivo amyloid load as assessed by Pittsburgh Compound B (PIB)-PET binding and CSF Ab42, with higher 11C PIB binding correlating with lower CSF Ab42 levels (Fagan et al 2006;Forsberg et al 2008;Grimmer et al 2009;Tolboom et al 2009). A similar relationship has been found between CSF Ab42 and binding of 18F FDDNP, a PET ligand believed to label both plaques and tangles (Tolboom et al 2009).…”
Section: Fluid Biomarkers and The Brainmentioning
confidence: 99%
“…4; Forsberg et al 2008;Koivunen et al 2008;Lowe et al 2009;Okello et al 2009;Tolboom et al 2009;Wolk et al 2009;Devanand et al 2010;Jagust et al 2010;Rowe et al 2010). Five of these studies included longitudinal clinical follow-up for 1-3 years on 155 MCI patients and showed that 57 of these 155 progressed to clinical AD (37%) and 53 of these 57 were amyloid positive at baseline (93%); only four of 54 amyloid-negative MCI patients progressed to clinical AD in these studies (7%) Koivunen et al 2008;Okello et al 2009;Wolk et al 2009;Jagust et al 2010).…”
Section: Utility Of Amyloid Pet In the Study Of Admentioning
confidence: 99%
“…Approximately 88.9% of the patients with progressive mild cognitive impairment were considered affected by 18 F-FDG PET, whereas 84.9% of stable patients had negative 18 F-FDG PET (Yuan et al, 2008). Another method for in vivo assessment of the extent of AD is the use of new radiotracers including the amyloid PET tracer Pittsburgh Compound B ( 11 C-PIB) for visualizing fibers Aβ (Morris et al, 2009, Kadir et al, 2011 or 2-(1-{6-[( 18 F-fluoroethyl)(methyl)amino]-2naphthyl}ethylidene) malononitrile ( 18 F-FDDNP) that has been reported to label not only amyloid but also neurofibrillary tangles (Tolboom et al, 2009), and these methods have generated new possibilities for early diagnosis of brain impairments. The first attempt to image brain Aβ accumulation in AD was reported by Friedland et al in 1997 using a monoclonal antibody fragment labelled with 99m Tc for single SPECT.…”
Section: E T E C T E D E I T H E R B Y V I S U a L I N S P E C T I O mentioning
confidence: 99%